Prevalence of Chronic Complications, Their Risk Factors, and the Cardiovascular Risk Factors among Patients with Type 2 Diabetes Attending the Diabetic Clinic at a Tertiary Care Hospital in Sri Lanka - Maulee Hiromi Arambewela; Noel P. Somasundaram; Hettiarachchige Buddhi Pradeep Ranjan Jayasekara; Mahesh P. Kumbukage; Pulukkutti Mudiyanselage Sarath Jayasena; Chandrasekara Mudalige Priyanka Hemanthi Chandrasekara; Kurukulasuriya Ravindra Alexis Sudath Fernando; Divadalage Priyantha Kusumsiri (Journal of Diabetes Research)
Diabetes incurs heavy burden to patients and the healthcare system. Assessment of disease burden is important in taking necessary precautions and management decisions. We aimed to determine the prevalence of macro- and microvascular complications, their risk factors, and coronary artery disease (CAD) risk factors among patients with type 2 diabetes mellitus (T2DM). A descriptive cross-sectional single-centre study was carried out among 3000 patients with T2DM attending the diabetic clinic at the National Hospital of Sri Lanka from January to July 2016. The study population had 72.7% females and 27.3% males. Mean age and disease duration were 58.3 ± 10.3 and 10.8 ± 7 years, respectively. Prevalence of CAD, stroke, and peripheral vascular disease were 10.6%, 1.1%, and 4.7% while diabetic retinopathy, neuropathy, nephropathy, diabetic foot, and lower extremity amputation (LEA) were 26.1%, 62.6%, 50.8%, 2.6%, and 1.3%, respectively. Prevalence of overweight/obesity, hypertension, dyslipidemia, and smoking were 80%, 77.6%, 76.7%, and 11%, respectively. Increased age, disease duration, and HBA1c were risk factors for microvascular disease and diabetic foot while age was the only risk factor for macrovascular complications. Occurrence of CAD, peripheral neuropathy, diabetic foot, and LEA was significantly higher among males than when compared to females. This study highlights the major burden of chronic complications and high prevalence of CAD risk factors in this population.